Miro1 deficiency in amyotrophic lateral sclerosis - Zhang, Fan; Wang, Wenzhang; Siedlak, Sandra L.; Liu, Yingchao; Liu, Jun; Jiang, Keji; Perry, George; Zhu, Xiongwei; Wang, Xinglong (Frontiers in Aging Neuroscience, 2015)
Proper transportation of mitochondria to sites with high energy demands is critical for neuronal function and survival. Impaired mitochondrial movement has been repeatedly reported in motor neurons of amyotrophic lateral sclerosis (ALS) patients and indicated as an important mechanism contributing to motor neuron degeneration in ALS. Miro1, a RhoGTPase also referred to as Rhot1, is a key regulator of mitochondrial movement linking mitochondria and motor proteins. In this study, we investigated whether the expression of Miro1 was altered in ALS patients and ALS animal models. Immunoblot analysis revealed that Miro1 was significantly reduced in the spinal cord tissue of ALS patients. Consistently, the decreased expression of Miro1 was also noted only in the spinal cord, and not in the brain tissue of transgenic mice expressing ALS-associated SOD1 G93A or TDP-43 M337V. Glutamate excitotoxicity is one of the major pathophysiological mechanisms implicated in the pathogenesis of ALS, and we found that excessive glutamate challenge lead to significant reduction of Miro1 expression in spinal cord motor neurons both in vitro and in mice. Taken together, these findings show Miro1 deficiency in ALS patients and ALS animal models and suggest glutamate excitotoxicity as a likely cause of Miro1 deficiency.